Transvaginal sonography in the diagnosis of endometrial pathology in menopausal women without uterine bleeding: depending on the duration of the menstrual period - Jędrzejczyk, Sławomir; Juchnowicz-Bierbasz, Romuald; Muchametczyn, Marek; Kisielewski, Karol; Lau, Katarzyna; Stetkiewicz, Tomasz; Słodki, Maciej (Menopause Review/Przegląd Menopauzalny, 2010)
Introduction : Endometrial polyps, submucous myomas, hyperplasia endometrium and endometrial cancer can proceed with or without bleeding or any other symptoms. All diseases can coexist with or lead to endometrial cancer. Aim : The aim of the study was to evaluate the usefulness of transvaginal sonography in the diagnosis of asymptomatic diseases in the uterus cavity in correlation with time after the last menstrual period. Material and methods : 59 postmenopausal women (min 1 year after menopause), without uterine bleeding, non HRT users, referred for hysteroscopy or D&C because of abnormal transvaginal sonography. Results : Average endometrium thickness in normal histopathology results was 8.8 ±4.5 mm (median 8) and was lower than in women with abnormal results (12.7 ±3.4 mm (median 13)) (p < 0.001). In a subgroup of 21 women fewer than 5 years after menopause, the average endometrium thickness in abnormal histopathology results was higher than in women with normal results (p 0.05). In a subgroup of 18 women after more than 14 years after menopause, the average endometrium thickness in normal histopathology results was 8.9 ±5.2 mm and in abnormal results it was 12.3 ±3.0 mm (p > 0.05). Conclusions: Usefulness of transvaginal sonography in the diagnosis of uterus cavity pathology in women without bleeding after menopause is higher until 5 years after menopause. Frequency of different pathologies existing in the uterus cavity depends on time since the last menstrual period. Endometrial thickness of up to 8 mm, as a single symptom in postmenopausal women without bleeding should be an indication for control TV ultrasound only. No histology is required.